Critical design and evaluation factors of mobile business models: "Road block" eradicators for mobile networks operators. Issue 5 (14th September 2015) - Al-Debei, Mutaz M.; Al-Lozi, Enas; Al-Hujran, Omar
Abstract : Purpose: – The purpose of this paper is to define critical design and evaluation factors of business models (BM) for mobile network operators (MNOs) in general, and more specifically for mobile data services. Design/methodology/approach: – This paper follows a qualitative approach. Aiming to identify critical design factors for mobile BMs, this research, as a part of larger research, examines three real-life cases related to mobile data service BM design and engineering. These cases are Orange Business Services (OBS); Apple's iPhone services and applications, and NTT DoCoMo's i-mode service. Findings: – In this paper, the authors provide a framework for designing and developing Market-Aligned, Cohesive, Dynamic, Explicit, and Unique BMs with Fitting Network-Mode, which, if adopted by MNOs, would ensure their long-term success by improving the sustainability and innovation capabilities of their BMs. These critical design factors address different spheres of the mobile business: "Cohesion" and "Explicitness" are operator-oriented, whereas "Market-Alignment, " "Dynamicity, " "Uniqueness, " and "Fitting Network-Mode" are industry-oriented. Research limitations/implications: – Although the paper provides in-depth analysis of three case studies in the context of mobile telecommunications, the authors cannot claim that the developed framework can be generalized to all services in the mobile telecommunications industry. Further validation through empirical testing is preferred and this could be done in future research. Practical implications: – The developed framework is of value to MNOs as it provides them with a holistic approach for designing and also evaluating successful BMs over time. This is because the developed framework defines critical design factors for BMs in the contexts of their environments. Originality/value: – The domain of BMs is still emerging within the field of information systems. The majority of prior studies either tackled the issue of BM definition or provided taxonomies and classifications of this concept. The originality of this paper comes from the fact that it takes further steps in developing the concept by providing a comprehensive framework which encapsulates critical design and evaluation factors of mobile BMs.